Improvement of adenoviral vector-mediated gene transfer to airway epithelia by folate-modified anionic liposomes - Zhong Z (Dove Medical Press, 2011)
Zhirong Zhong1,2, Yu Wan1, Jianfeng Han1, Sanjun Shi1, Zhirong Zhang1, Xun Sun11Key Laboratory of Drug Targeting and Drug Delivery Systems, Ministry of Education, West China School of Pharmacy, Sichuan University, Chengdu, Sichuan, People's Republic of China; 2Luzhou Medical College, Luzhou, Sichuan, People's Republic of ChinaAbstract: Despite remarkable progress in the development of both viral and nonviral gene delivery vectors for airway disease treatment, poor gene transfer efficiency to the airway epithelium is a major obstacle in clinical application. To take advantage of the unique features of viral and nonviral vectors, we have developed complexes of adenovirus vector and anionic liposomes (AL-Ad5) by the calcium-induced phase change method. In the current study, based on the fact that there are overexpressed folate receptors on the surface of airway epithelia, we further modified the AL-Ad5 complexes with folate (F-AL-Ad5) to improve the transduction ability of Ad5 in airway epithelia. The transduction efficiencies of the obtained F-AL-Ad5 and AL-Ad5 complexes were assessed in primary-cultured airway epithelia in vitro. Our results indicated that compared with naked adenovirus vector, both AL-Ad5 and F-AL-Ad5 could significantly enhance the gene transduction efficiency of adenovirus vector in primary-cultured airway epithelial cells. Moreover, the enhancement mediated by F-AL-Ad5 was more dramatic than that by AL-Ad5. These results suggested that F-AL-Ad5 may be a useful strategy to deliver therapeutic genes to the airway epithelia and is promising in clinical application.Keywords: gene delivery, adenovirus vector, folate receptor, primary-cultured airway epithelia